(3x + 5)(x2 - 2)
(x^18 - 6x^9 + 18)(x^18 + 6x^9 + 18)
There is no rational solution.
The idea is to add like terms together - in this case, the terms that have the variable "x" raised to the same power.
your equation is this... x3 + 5x2 = 6x get all the terms on the left side x3 + 5x2 - 6x = 0 now factor out an "x" x(x2 + 5x - 6) = 0 now factor the equation inside x(x + 6)(x - 1) from this you can find your x-values x= 0, -6, and 1 now that you have your x-values your equation is solved. just use algebra to get all of the terms on the one side. then factor out anything that is common in all of the terms. then factor the polynomial. then find what values for "x" that satisfy the equation.
As written, that's 3x^3 - 12x which factors to 3x(x - 2)(x + 2)
5x2 - 16x + 12 = 5x2 - 10x - 6x +12 = 5x(x - 2) - 6(x - 2) = (x - 2)(5x - 6) Whether or not these are in descending order depends on the value of x.
xx+3x+7=6x+18 xx+3x+7-(6x+18)=6x+18-(6x+18) xx-3x-11=0 Factors of -11: 1,-11 -1,11 Doesn't factor evenly, use quadratic
I'm not sure this was notated correctly. As written, this is -11x plus or minus 18, which doesn't factor.
(x3+5x2+6x)/x to get x(x2+5x+6) find numbers that multiply to 6 and add to five (2 and 3) your factors are x, x+2, and x+3